Pentingnya mengembangkan keterampilan mendengarkan efektif dalam konseling - Yenti Arsini; Zachra Aulia; Tara Latifah Nur Qulby; Dewi Purnama Sari (JURNAL EDUKASI NONFORMAL, 2023)
Effective communication skills are crucial in counseling sessions as they play a pivotal role in facilitating the success of counseling. Among the fundamental skills required in counseling, listening skills stand out. These skills enable counselors to not only comprehend and interpret the messages conveyed by those they counsel but also respond appropriately. This, in turn, fosters trust, comfort, and support, encouraging individuals to open up about their challenges. Furthermore, effective listening is instrumental in demonstrating empathy during the counseling process. However, in practice, there are several potential obstacles to listening, such as preconceived notions about clients, anticipating their words instead of truly hearing them, being preoccupied with one's own thoughts, personal issues, strong emotional reactions, or distractions like office noise or hunger. Within the realm of counseling skills, honing the ability to listen effectively is of paramount importance and serves as a foundational skill to nurture throughout the counseling relationship, ultimately enhancing empathy and ensuring appropriate responses.